Effects of barley green on uric acid, inflammatory factors, xanthine oxidase activity and body composition of patients with hyperuricemia: a randomized controlled trial - Cui, Mingxuan; Shao, Lin; Zhao, Shilong; Guo, Qianying; Liu, Xinran; Liu, Peng (Frontiers in Nutrition, 2025)
AimThis study aims to evaluate the efficacy of barley green intervention in reducing uric acid (UA) levels, as well as its effects on related inflammatory factors, metabolic indices and body composition in individuals with hyperuricemia. Additionally, we investigate the mechanism of action associated with xanthine oxidase (XOD).Materials and methodsIn this randomized controlled trial, patients diagnosed with hyperuricemia were randomly assigned to either an intervention group receiving barley green alongside a balanced diet regimen or a control group adhering solely to a balanced diet. Comprehensive clinical data were collected from participants, and nutritional measurements, UA metabolism-related indicators, inflammatory factor levels, and XOD activity were assessed at various stages over a 3-month period.ResultsA total of 90 subjects participated in the study; 49 individuals were included in the intervention group while 25 comprised the control group. The reduction in UA levels-the primary endpoint-was significantly greater after 3 months of intervention compared to those following only a balanced diet [55.00 ± 62.39 vs. 25.00 ± 59.52 (p = 0.049)]. Improvements in XOD activity and body composition were also observed within the intervention group relative to controls. Multiple linear regression analysis indicated that baseline UA levels, XOD activity, leptin concentrations, as well as changes in total cholesterol and body weight were independently associated with the reduction in UA following a 3-month intervention.ConclusionOral administration of barley green may contribute to UA regulation and improvements in body composition among individuals with hyperuricemia, with the reduction in XOD activity potentially serving as one of the underlying mechanisms by which barley green exerts its urate-lowering effect.Clinical trial registrationClinicalTrials.gov, identifier NCT06876909.